Vpliv skupine G20 na mednarodne ekonomske odnose - Čuden, Peter (Vojaškošolski zbornik, 2024)
The economic globalization outlined in the Bretton Woods Conference laid the foundations for new international economic systems promoting international trade and financial stability. The collapse of the Bretton Woods system and the subsequent political changes, including the neoliberal revolution, further strengthened demands for economic integration. It was in the grip of these demands, as a result of calls to fully integrate major developing countries and other systemically important countries, and as a reflection of the new global economic and political reality, that the G20 was established to address financial and economic issues that transcended national borders. Bringing together the world's key economies, the G20 is effectively becoming a major international cooperation forum with a complex structure which is adapting to global challenges and aspirations while continuing to strengthen its role in the international economy, despite the criticism of some experts.
Keywords: economic community; ekonomska skupnost; G20; globalizacija; globalization; Mednarodne organizacije; Mednarodni gospodarski odnosi; Mednarodni odnosi; Regionalizem (mednarodna skupnost); skupina dvajsetih; the Group of Twenty